The effects of combinations of a green tea extract and an active ingredient thereof, with standard antiretroviral drugs on SC-1 cells infected with the LP-BM5 virus - Bester, Megan J. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.